IMPLEMENTASI BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN WISATAWAN MENGUNJUNGI OBJEK WISATA PULAU PASUMPAHAN - Henryanto Abaharis; Elsa Meirina (JURNAL PUNDI, 2019)
ABSTRACT The development of tourism business can have a positive impact in the effort to contribute to the country's foreign exchange earnings, increasing business opportunities and new jobs, increasing government and community revenue. The purpose this study is to determine whether the influence of the implementation of service marketing mix (product, price, place, promotion, people, process and physical evidence) affect the decision of tourists visiting the tourist object of Pasumpahan island. In this study this population refers to tourists who have visited the tourist object Pasumpahan Island, samples taken as many as 100 respondents using convenience sampling techniques. Data analysis techniques used are observations, questionnaires and documentation. Method used in this study is multiple linear regression analysis , the results obtained show that the product, price, place, process has no significant effect on the purchase decision, while promotion, people and physical evidence significantly influence the purchase decision. Keywords : Product, Price, Promotion, Place, People and Physical Evidence influence the purchase decision.